Brief ICF Core Set for Schizophrenia: Development of Criteria for Assessing the Degree of Disability - Lara Pinho; Manuel Lopes (Karger Publishers, 2022)
Introduction: A paradigm shift in the assessment and rehabilitation of people with schizophrenia is needed, with an integrative perspective rather than a simple focus on the underlying symptomatology. To this end, it is essential to adopt integrated and continuous care focused on the person in his/her context. As a contribution, the Brief International Classification of Functioning, Disability and Health (ICF) Core Set for schizophrenia has been developed by international experts. The present study aims to develop a scale to classify the degree of disability for each of the categories of the Brief ICF Core Set for schizophrenia. Methods: The classification criteria were first developed by the researchers and then submitted for assessment by national experts in the area of schizophrenia, using the modified e-Delphi method. Results: Two rounds of questions were asked, and a consensus was reached on the development of the Schizophrenia Functioning Core Set, consisting of all categories of the Brief ICF Core Set for schizophrenia and the criteria for classifying the degree of disability. The degree of agreement of the experts was greater than 90% in all categories. Conclusion: The construction of the disability grading criteria was based on the characteristics of schizophrenia as defined in DSM-V, as well as on some functional assessment scales specifically for this disorder. The development of the Schizophrenia Functioning Core Set allows for reducing the subjectivity in the assessment of the functioning of people with schizophrenia, standardizing the application of criteria to assign the degree of disability in each of the categories.